The associations of social support and other psychosocial factors with mortality and quality of life in the dialysis outcomes and practice patterns study - Untas, Aurélie; Thumma, Jyothi; Rascle, Nicole; Rayner, Hugh; Mapes, Donna; Lopes, Antonio A; Fukuhara, Shunichi; Akizawa, Tadao; Morgenstern, Hal; Robinson, Bruce M; Pisoni, Ronald L; Combe, Christian (Clinical journal of the American Society of Nephrology, 2011)
This study aimed to investigate the influence of social support and other psychosocial factors on mortality, adherence to medical care recommendations, and physical quality of life among hemodialysis patients. Data on 32,332 hemodialysis patients enrolled in the Dialysis Outcomes and Practice Patterns Study (1996 to 2008) in 12 countries were analyzed. Social support and other psychosocial factors related to ESRD and its treatment were measured by patient self-reports of health interference with social activities, isolation, feeling like a burden, and support from family and dialysis staff. Cox regression and logistic regression were used to examine associations of baseline social support and other psychosocial factors with all-cause mortality and with other measured outcomes at baseline, adjusting for potential confounders. Mortality was higher among patients reporting that their health interfered with social activities, were isolated, felt like a burden, and were dissatisfied with family support. Poorer family support and several psychosocial measures also were associated with lower adherence to the prescribed hemodialysis length and the recommended weight gain between sessions. Some international differences were observed. Poorer self-reported social support and other psychosocial factors were associated with poor physical quality of life. Poorer social support and other psychosocial factors are associated with higher mortality risk, lower adherence to medical care, and poorer physical quality of life in hemodialysis patients. More research is needed to assess whether interventions to improve social support and other psychosocial factors will lengthen survival and enhance quality of life.